The effect of binge-watching on the subscription of video on demand: results from randomized experiments - Matos, Miguel Godinho de (2021)
We analyze the outcomes of two randomized field experiments to study the effect of binge-watching on subscription to video on demand. In both cases, we offered access to subscription VoD (SVoD) to a random set of households for several weeks and used another random set of households as a control group. In both cases, we find that the households that binge-watch TV shows are less likely to pay for SVoD after these free trials. Our results suggest that binge-watchers deplete the content of interest to them very quickly, which reduces their short-term willingness to pay for SVoD. We also show that recommendation reminders aimed at widening the content preferences of households offset the negative effect of binge-watching and lessen the concerns of binge-watchers with lack of content refresh. We discuss that these recommendation reminders may help content providers manage supply costs, which may otherwise become prohibitive with frequent updates to SVoD catalogs.